A low spin manganese(iv) nitride single molecule magnet. Issue 9 (17th June 2016) - Ding, Mei; Cutsail III, George E.; Aravena, Daniel; Amoza, Martín; Rouzières, Mathieu; Dechambenoit, Pierre; Losovyj, Yaroslav; Pink, Maren; Ruiz, Eliseo; Clérac, Rodolphe; Smith, Jeremy M.
Abstract : Structural, spectroscopic and magnetic methods have been used to characterize the tris(carbene)borate compound PhB(MesIm)3 MnN as a four-coordinate manganese(iv ) complex with a low spin ( S = 1/2) configuration. Abstract : Structural, spectroscopic and magnetic methods have been used to characterize the tris(carbene)borate compound PhB(MesIm)3 MnN as a four-coordinate manganese(iv ) complex with a low spin ( S = 1/2) configuration. The slow relaxation of the magnetization in this complex, i.e. its single-molecule magnet (SMM) properties, is revealed under an applied dc field. Multireference quantum mechanical calculations indicate that this SMM behavior originates from an anisotropic ground doublet stabilized by spin–orbit coupling. Consistent theoretical and experiment data show that the resulting magnetization dynamics in this system is dominated by ground state quantum tunneling, while its temperature dependence is influenced by Raman relaxation.